Matrix Stiffness Induces Pericyte-Fibroblast Transition Through YAP Activation - Feng, Feng; Feng, Xueyan; Zhang, Di; Li, Qilong; Yao, Li (Frontiers in Pharmacology, 2021)
Vascular pericytes, important mural cells that retain progenitor cell properties and protect vascular integrity in healthy tissues, are often associated with tumor development, but their functions in cancer invasion remain elusive. One prominent outcome of tumor occurrence is that the microenvironment of the lesion often stiffens, which could change resident cell behavior. Here, we found pericytes are matrix stiffness-responsive and mechanical stimuli induce pericyte-fibroblast transition (PFT). Soft PA gels that mimic the stiffness of healthy tissues retain the identity and behavior of pericytes, whereas stiff PA gels that reflect the stiffness of tumorous tissues promote PFT and the mobility and invasiveness of the cells. Matrix stiffness-induced PFT depends on the activation of YAP (Yes-associated protein), a transcription factor, which, upon receiving mechanical signals, transfers from cytoplasm to nucleus to mediate cell transcriptional activities. Our result reveals a mechanism through which vascular pericytes convert to fibroblasts and migrate away from vasculatures to help tumor development, and thus targeting matrix stiffness-induced PFT may offer a new perspective to the treatment of cancer metastasis.